Population fluctuation of fruit-flies in orchard of guava in Pindorama - SP - Duarte, Rogerio Teixeira [UNESP]; Machado Baptista, Ana Paula [UNESP]; Pazini, Wilson Carlos [UNESP]; Galli, Julio Cesar [UNESP] (Univ Fed Grande Dourados, 2015)
Knowledge about the population fluctuation of fruit flies (Diptera: Tephritidae) is an important tool in the adoption of control methods recommended by Integrated Pest Management (IPM). The aim of this research was to study the population fluctuation of fruit flies and their correlation with meteorological elements in orchard of guava located in Pindorama - SP. The research was conducted between September 2008 and July 2009. We installed randomly in that experimental area five yellow stick traps for monitoring adult fruit flies, spaced 30 m from each other in an experimental area with approximately two hectares. These traps were replaced every two weeks and conducted at the Laboratory of Ecological Selectivity of the Department of Plant Protection (FCAV/UNESP) for evaluation of the specimens sampled. The population density of adult fruit flies was analyzed in histograms and correlated with meteorological elements, minimum, medium and maximum temperature (degrees C) and accumulated precipitation (mm). Anastrepha spp. was predominant in comparison to Ceratitis capitata, with high population density in the fructification period. There was correlation between the population fluctuation of C. capitata with the meteorological element minimum temperature.
Keywords: Anastrepha spp.; Ceratitis capitata; meteorological elements; orcharding; population monitoring